PENGARUSUTAMAAN GENDER DALAM PEMBANGUNAN PERTANIAN : KASUS PADA PELAKSANAAN PROGRAM FEATI DI KABUPATEN MAGELANG - Dian Maharso Yuwono (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
Efforts  to  improve  the  effectiveness  and  efficiency  of  utilization  of agricultural  resources  in  order  to  accelerate  the  increase  in  the  welfare  of  farmers cannot  be  separated  from  the  role  of  women  in  agricultural  development.  Gender mainstreaming  in agricultural development is mandated by  Presidential Decree No. 9 of  2000.  This  decree  is  a  strategy  to  achieve  gender  equality  in  development.  The gender  aspects  must be integrated  in policy formulation  and  program  activities  from planning  to  evaluation.  This  paper  aims  to  reveal  the  women  role  in  the  program implementation  of  Farmer  Empowerment  through  Agricultural  Technology  and Information  (FEATI)  in  Magelang  District-Central  Java  that  integrates  gender mainstreaming.